UJI KANDUNGAN KHLORIDA PADA AIR MINUM DALAM KEMASAN (AMDK) PRODUKSI PANTAI BARAT SELATAN ACEH - Zaulfikar Abbas; Muhamad Reza (Jurnal Optimalisasi, 2016)
The content of chloride in drinking water, including the Bottled Drinking Water (bottled water) must correspond Ministry of Health of the Republic of Indonesia number 492/Menkes/PER/ IV/2010, which should not exceed 250 mg/l. Excess chloride load in the body are harmful to health. Therefore, the testing of any content of chloride in drinking water should always be done properly and responsibly.Based on the Decree No. 492 of 2010, researchers wanted to determine the content of chloride from 7 (seven) brands of Bottled Drinking Water (bottled water) local production region south west coast of Aceh province. The results of the study illustrate that the chloride load on Bottled Drinking Water (bottled water) that exceed 250 mg / l or not, so that eventually we can conclude the seven brands of Bottled Drinking Water (bottled water) is feasible or not feasible consumed by the public.To execute this research, researchers using the descriptive method is based on laboratory test results. The sampling technique is purposive sampling, where each brand is taken three (3) samples of drinking water in glass packaging 220-230 ml from markets / locations. The results of observations, researchers found seven brands of Bottled Drinking Water (bottled water). Tests conducted repetition 2 times. So the total number is 42 samples tested.The results showed that from 42 samples against the chloride load test results may vary from 11.3032 to 25.4322 mg / l. The content is still very low compared with drinking water quality standard specified in Permenkes 492 in 2010, which does not exceed 250 mg / l. From the results obtained it can be concluded that the seven brands of Bottled Drinking Water (bottled water) production region of the South West Coast of Aceh is safe for public consumption because the content is still very low khlordanya from quality standards established Ministry of Health of the Republic of Indonesia.Keywords: chloride, bottled water